Interaural Stacked Auditory Brainstem Response Measures for Detecting Small Unilateral Acoustic Tumors - Don, Manuel (S. Karger AG, 2011)
The Stacked auditory brainstem response (SABR) was developed and investigated as a screening tool for small (≤1 cm) unilateral acoustic tumors (vestibular schwannomas) that were missed by standard clinical auditory brainstem response (ABR) measures [Don et al.: Am J Otol 1997;18:608–621; Audiol Neurotol 2005;10:274–290]. While the SABR measure provided much greater sensitivity than the standard ABR measures for small tumor detection, we believed that the large intersubject variability of the SABR measure compromised both the sensitivity and specificity of the measure. However, as we demonstrate in this paper, the variability between ears of a given individual is small. Thus, we introduced an interaural SABR (ISABR) amplitude difference measure to improve the sensitivity and specificity of the SABR amplitude measure to detect small unilateral acoustic tumors. Its main advantages are two-fold. First, it is somewhat immune to variables that affect the absolute SABR amplitudes because it is a relative measure. Second, it is better at assessing tumor patients with very large and non-tumor patients with very small absolute SABR amplitudes. We believe that the ISABR is a useful addition to ABR measures aimed at detecting the presence of unilateral acoustic tumors.